The Image of the Empire in Dalmatian hagiography: A contribution to the question of Byzantine presence in the Adriatic (600-1200) - Vedriš, Trpimir (2008)
According to very simplified and more or less accepted narrative, the eastern Adriatic coast was a part of the Byzantine Empire between the sixth and late twelfth centuries, leading to the expectation of traces of either Byzantine literary influences or “ Byzantine sentiment” (in the form of douleia or oikeiosis) in the regional intellectual and spiritual production. This however seems to be, to a large extent absent from the corpus of hagiographic texts. The scope and the nature of the Byzantine presence in medieval Dalmatia and Istria are examined here through cults of saints A “ two-track inquiry” positions saints’ cults in their broader historical context (types of evidence, establishment, dispersion), and then scrutinizes the corpus of local hagiographic texts. What is central to this approach is a close reading of the local hagiographic texts, and, through a narrative analysis, attempting to discern an image of the empire as an expression of a hypothetical Byzantine sentiment or a sense of belonging to the empire. Although both are taken into consideration, a distinction is made between the hagiographic sources as understood in a broader sense (hagionymy, hagio-topography, iconography, liturgy, and sigillography) and hagiography stricte dictum, meaning exclusively the “ hagiographic” texts. While the latter remains central to the inquiry, the former requires attentive investigation since it promises to clarify the broader historical context of the emergence and development of the cults. The starting point of the research is the fact that the majority of the urban patron saints in this period were of East Roman/Byzantine origin (e.g. Rovinj (Mons rubeus) – St. Euphemia of Chalcedon, Rab (Arba) – St. Christophorus ; Zadar (Iadera): St. Anastasia of Sirmium (here one might add Sts. Chrysogonus and Zoilus of Aquileia, Agape, Chonia and Irene of Thesaloniki), Trogir (Tragurium) - St. John the Almsgiver of Alexandria ; Split (Aspalatum) - St. Domnius of Antioch ; Dubrovnik (Ragusa) - St. Sergius and Bacchus, Kotor (Decatera) - St. Trypho). Although in the terms of hagio-topography the region seems very “ Byzantine, ” different types of sources give substantially different evidence and allows almost contradictory conclusions about the nature of the Byzantine presence in the Adriatic. While there is, indisputably, a “ thick layer” of Byzantine saints in Dalmatia (attested both in hagio-topography and liturgy), the preserved liturgical evidence dedicated to them rarely consists of elements of the Greek liturgy or other elements of the cult typical for the Byzantine empire. It must be stressed, likewise, that most of the preserved local hagiographic texts connected to these saints are written in Latin. Moreover, according to typology, form, etc. they seem to fit Latin rather then Greek hagiographic patterns. Departing from the proposed issues the paper aims at contributing to a broader scholarly discussion about the scope and the nature of the Byzantine presence in Medieval Dalmatia and Istria
Projekt MZOS
ENG